Desarrollo e implementación de una aplicación móvil para la oferta de servicios publicitarios del sector comercial del cantón La Maná mediante arquitectura de microservicios de geolocalización en tiempo real para la Universidad Técnica de Cotopaxi. - Barrera Landa, Christian Ernesto (2021)
The objective of this research is to implement a mobile application based on the offers of advertising services and focused on geolocation microservices which is necessary to take into account as a starting point and to encourage Pymes the use of current technologies and media. At present, a globalized world is made constantly by the great technological advances. Communication ways that correspond to mobile applications are discovered througt mobie operating systems, this research is focused on defining problems with the application and use of advertising-based electronic commerce and the creation of virtual catalogs by Pymes in La Maná Cantón. For this reason, a mobile application was developed on the Android platform, as a real-time data storage, the services on firebase real time cloud, all and the implementation of geolocation microservices on the Google Cloud platform, all these tools allow to obtain effective results which guarantee the fulfillment of the planed objective. Finally, a commercial advertising application composed of real-time geolocation microservices was implemented that will allow to establish a set of information and location of businesses directed to the public in general, a good offer of the availability of catalogs of products and services, and the possibility of accessing from anywhere and having the opportunity to watch the advertising content of its affiliates.